Model Self Management Education (SME) Dalam Meningkatkan Kemampuan Deteksi Dini Hipoglikemia Pada Diabetesi Di RSUD Dr Moewardi Surakarta - Siti Lestari; Tri Sunaryo (Poltekkes Kemenkes Surakarta, 2016)
Abstract: Self-Management Education, Hypoglycemia. Diabetes Mellitus is a metabolic disease that needs attention and care for a long time in order to prevent complications. People with DM must have good knowledge, skill, and behavior so they can manage their life by themselves. Research showed that 50–80%, people with DM have not enough knowledge to manage their disease. Through the self-management, people with diabetes can improve their competence in early detection of hypoglycemia so it would increase the quality of life and reduce the risk of developing complications. The purpose of this study was to investigate the impact of diabetes self-management education toward early detection of hypoglycemia among patients with diabetes. A quasi-experimental pre and post design with a control group was used to investigate the impact of using education on self-management. The participants were 40 that divided into intervention and control group. Purposive sampling was used to take the samples. T-Test was used to analyze the data. The competence of diabetes in early detection of hypoglycemia was an increase, from 6,1 with SD 13.7 to 71,7 with SD 19.2. Then, the model of Self Management education influenced the competence of people with diabetes in the early detection of hypoglycemia, P value 0,011 (α = 0,05). The findings demonstrate that self-management education could improve the competence of diabetes in the early detection of hypoglycemia.